The main Vectors of Further Development of the Union State - O. G. Karpovich; T. V. Vershinina (Проблемы постсоветского пространства)
The Union State of Belarus and Russia is the oldest of the existing integration associations in the Eurasian space and, undoubtedly, is one of the foundations of the emerging architecture of Eurasian integration. During the period of its existence, the Union State has done a lot of work on the path of rapprochement of fraternal peoples, and even more ambitious tasks are to be implemented. This article examines the main problems of the Union construction, analyzes the key areas of cooperation between the member states of the Union State. The impressive advanced integration experience of the Union State in social, military-political, scientific-educational, as well as in a number of areas of the economic sphere can be used in the implementation of integration initiatives within other Eurasian regional associations and is extremely important and in demand precisely during the transition to multipolarity and the formation of the Eurasian center on the world stage. The Union State is a fraternal relationship proven over the years, built on mutual respect, attention to problems, joint achievements and the implementation of plans to mobilize common potential, guaranteed support in difficult periods without waiting for immediate returns. The benefits of such relations are achieved not only by scaling the market, conducting a coordinated foreign trade and technical policy, characteristic of the participants of “ordinary” economic associations. The predictability and trust inherent in fraternal friendship make it possible, for example, to lower individual thresholds for economic (and not only) security, since the reliable functioning of the economy is achieved together.